NUTRIENT DIGESTIBILITY AND GROWTH PERFORMANCE OF BROILER CHICKENS FED PROCESSED TROPICAL SICKLE POD (SENNA OBTUSIFOLIA (L) SEED MEAL - Clement, Augustine; Dankasa, Kwari Ibrahim; Uchei, Igwebuike Joseph; Bala, Adamu Shuaib; Siaka, Diarra Seriba (Journal of Agricultural Sciences (Belgrade), 2017)
Eight weeks feeding trial was conducted to evaluate the nutrient digestibility and growth performance of broiler chickens fed raw or processed Senna obtusifolia seed meal (SOSM). Six experimental diets were compounded to contain 0% SOSM and 20% each of the raw, boiled, soaked, sprouted and fermented SOSM respectively. Two hundred and sixteen (216) broiler chicks were randomly allotted to six (6) dietary treatments in a randomized complete block design with three (3) replicates containing 15 chicks each. Data were collected on nutrient digestibility, feed intake, weight gain, feed conversion ratio and mortality. The result of productive performance indicated that feed intake, weight gain and feed conversion ratio were significantly (P